Nutrient Composition, Amylose Content and Pasting Characteristics of Some Elite Accessions of Nerica Rice - J.C, Anuonye; C.E, Chinma; J, Olukayode; A, Suleiman (Journal of Food Technology Research, 2016)
Eighteen elite lines of Nerica rice were assessed for proximate, amino acid composition, amylose content and pasting viscosity. The aim was to nominate the lines for further multilocational yield trails and eventual release as varieties. The lines were parboiled by soaking in hot water (75oC) for 9-20hrs and then steamed for 40-45minutes at75oC in a steamer. Raw and parboiled samples were dehusked and polished and used in subsequent evaluations. The results indicated that protein varied from7.47+0.21to 11.73+0.15% parboiled samples and from 6.87+ 1.01to 11.65+ 0.51% for the unparboiled or raw samples. Fat also varied from 5.57+ 4.22- 6.00+ 0.54 the parboiled samples and from 5.33 to 6.33+ 0.5% for the unparboiled samples. The amino acid profile showed that both parboiled and unparboiled samples met the Food and Agricultural Organization (FAO) requirements for infants, adolescent and adults for histidine, threonine, valine and isoleucine and leucine. Both samples and the check were however deficient in lysine (4.01-4.60). Parboiling did not significantly (p<0.5) improve the proximate and amino acids composition of samples. The unparboiled milled samples had higher amylose content (23.84 – 50.85%) compared to(12.85 – 31.81%) of the parboiled samples. The amylose content of the parboiled samples placed them in the intermediate amylose category. The pasting properties showed that raw samples exhibited conventional non-waxy cereal pasting characteristics while the parboiled samples indicated destructuring in the pasting profile. The results were indicative that the NERICA LINES would have high cooking qualities.